ANALISIS NILAI NASIONALISME DAN DEIKSIS PADA FILM BUYA HAMKA VOL.1 KARYA ALIM SUDIO - Amanda Maharani Putri; Nanang Maulana; Purlilaiceu (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to analyze the values of nationalism and the use of deixis in the film Buya Hamka Vol. 1 directed by Alim Sudio, as well as to explore its potential as learning material in Indonesian language classes at junior high school. Nationalism is reflected through characters’ attitudes, behaviors, and dialogues that emphasize patriotism, unity, and cultural appreciation. Meanwhile, deixis is observed as an important linguistic aspect in understanding the context of communication between characters. The research employed a qualitative descriptive method with data collected through documentation and note-taking techniques. The findings indicate that the film contains various forms of nationalism values, such as love for the homeland, unity, religiosity, and willingness to sacrifice for the nation. In addition, the film presents different types of deixis, including personal, spatial, temporal, and social deixis, which function to clarify the meaning of dialogues and strengthen the narrative. The integration of nationalism values and deixis analysis in the film can be utilized as teaching material in Indonesian language learning, particularly in developing students’ character and linguistic competence. This research highlights that films with historical and cultural contexts, such as Buya Hamka Vol. 1, are not only entertaining but also educational, providing meaningful contributions to both language learning and character education in schools.